2019
DOI: 10.1002/adfm.201807964
|View full text |Cite
|
Sign up to set email alerts
|

Pushing PbS/Metal‐Halide‐Perovskite Core/Epitaxial‐Ligand‐Shell Nanocrystal Photodetectors beyond 3 µm Wavelength

Abstract: PbS nanocrystals have been proven to be highly suitable for photodetector fabrication by facile solution processing, and have been successfully tested as photosensitive material in imaging devices. So far, their spectral response has been blue-shifted with respect to that of commercial bulk PbS detectors, due to quantum confinement in nanostructures smaller than the exciton Bohr radius. Here, a PbS nanocrystal synthesis approach is introduced, allowing to surpass this limit, and thus to push the cut-off wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…Narrow band gap nanocrystals [1][2][3] are currently generating a strong interest for the design of high performance and low cost infrared sensors in the short-wave (SWIR: up to 1.7 µm) and mid-wave infrared (MWIR : 3-5 µm). 4,5 Recent developments include high detectivity photodiodes, 6 multicolor devices, [7][8][9] demonstration of focal plane arrays 10 and detectors with enhanced light matter coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Narrow band gap nanocrystals [1][2][3] are currently generating a strong interest for the design of high performance and low cost infrared sensors in the short-wave (SWIR: up to 1.7 µm) and mid-wave infrared (MWIR : 3-5 µm). 4,5 Recent developments include high detectivity photodiodes, 6 multicolor devices, [7][8][9] demonstration of focal plane arrays 10 and detectors with enhanced light matter coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Lead sulfide (PbS) CQDs have an absorption that is tunable from 1–3 μm (Fig. ) , and their photoconductors, 6 phototransistors, 7 and photodiodes 8 have demonstrated sensing capabilities from the visible to short‐wave infrared (SWIR) spectral regions. Despite the progress with PbS CQDs, their quantum efficiency—that is, the percentage of light detected and converted to measurable signal—is quite low, with values of 10–15 percent compared to 65–80 percent for epitaxial InGaAs (Fig.…”
Section: Making Strides Toward Commercial Cqd Ir Imagingmentioning
confidence: 99%
“…Unless otherwise specified, the data presented are for a detector operating at room temperature. Green circle = HgTe CQD photodiodes; 12 , 13 green triangle = phototransistors; 11 green square = photoconductors; 10 blue circle = PbS CQD photodiodes; 8 blue triangle = phototransistors; 7 blue square = photoconductors; 6 red circle = HgCdTe photodiodes; 14 , 15 orange circle = InGaAs photodiodes; 16 , 17 and yellow circle = InSb photodiodes 18…”
Section: Making Strides Toward Commercial Cqd Ir Imagingmentioning
confidence: 99%
“…Here, PbS is a particular attractive candidate due to its narrow bandgap and the potential for multiple exciton generation . Similarly, CQDs allow for the precise tuning of the photodetector sensitivity to a desired photon energy . It was furthermore shown that bandwidth limitations due to their modest carrier mobilities could be overcome when using CQCs in synergy with 2D materials, such as graphene or transition metal dichalcogenides …”
Section: Colloidal Quantum Dots For Optoelectronicsmentioning
confidence: 99%